Comparative analysis of isometric muscle strength and hamstring-to-quadriceps ratio between sexes in Crossfit® practitioners (Movimenta (ISSN 1984-4298), 2026)
CrossFit®, a high-intensity functional training program, enhances physical capabilities. However, muscle deficits can increase the risk of injuries and symptoms (pain). The objective was to compare the isometric muscle strength and the hamstrings-to-quadriceps ratio (H:Q) between male and female CrossFit® practitioners. Methods: This was a cross-sectional, analytical study with CrossFit® practitioners. We collected sociodemographic data, a history of lower limb injuries, and pain intensity (Visual Analog Scale - VAS). Quadriceps (Q) and hamstring (H) strength was assessed using isometric dynamometry to calculate the conventional ratio (H:Q). Results: The sample had a mean age of 28.8 ± 6.2 years and a BMI of 27.3 ± 5.4 kg/m². Males showed greater quadriceps and hamstring muscle strength than females, while the H:Q ratio did not differ between the sexes. Both males and females showed a high prevalence of muscle imbalance in the lower limbs. Pain and a history of lower limb injury were reported by 41.7% and 37.5% of the sample, among males and females, respectively (p < 0.05). Knees were the most affected joint (20.8%) in both sexes. The pain intensity in the sample was 0 (0-3.5). Conclusion: There was a difference in muscle strength between the sexes, and the study revealed a high prevalence of muscle imbalance (H:Q ratio < 0.6) in both sexes.
Keywords: musculoskeletal pain; muscle strength